PERENCANAAN ARSITEKTUR SISTEM INFORMASI SUMBER DAYA MANUSIA (SDM) DENGAN METODE FRAMEWORK TOGAF (STUDI KASUS : PUSAT PENGEMBANGAN SUMBER DAYA MANUSIA APARATUR KEMENTRIAN ENERGI DAN SUMBER DAYA MINERAL) - Endrawan Satria Mandala Putra; Hery Wahyudi (Jurnal Computech & Bisnis (e-Journal), 2020)
Information Systems Architecture is an understanding of all the different elements that support enterprise development and how these elements relate. in the development of enterprise architecture modeling requires a framework in the hope of being able to manage complex systems and be able to align the Information Systems business to be developed. The Open Group Architecture Framework (TOGAF) is a framework that provides methods and tools for building, managing and implementing and maintaining enterprise architecture. The key elements of TOGAF are Architecture Development Method (ADM) which includes several stages, namely Preliminary Framework and Principle, Stages (A) Architecture vision, Stages (B) Business Architecture, Stages (C) Information System Architecture, Stages (D) Technology Architecture, Stages (E) Opportunities and Solutions, Stages (F) Migration Planning. Information Systems Architecture Modeling in PPSDM with TOGAF produces Preliminary Framework and Principles produce the organization's enterprise scope in the form of main processes and supporting processes, Architecture Vision defines the organization's profile, defines the vision and mission, organizational goals, organizational structure, current state of the technology system architecture which includes 5 types of applications and computer networks. Business Architecture defines business architecture which includes the acceptance of training participants, teaching and learning activities, staffing, administration of letters and archives, finance, infrastructure. Information System Architecture includes data architecture there are 29 entities and application architecture there are 8 applications. Technology Architecture defines the application platform and network topology. Offortinuties and Solution, explain the benefits of the information system currently underway with the proposed information system. Migration Planning plans the technology transfer process by determining the implementation roadmap. Keywords: Enterprise, TOGAF, ADM, ArchitectureDOI : http://doi.org/10.5281/zenodo.4320189